Efeito alelopático de plantas de cobertura na inibição de plantas daninhas ocorrentes em soja - Bianchini, Alexandre (2017)
Allelopathy can be used in agriculture to control weeds, inhibiting their germination and / or emergence. In this sense, we tried to contribute with facts and data that help the application of weed control practice. A laboratory experiment with aqueous extract of four soil cover plants: Avena strigosa, Cichorium intybus, Chenopodium quinoa and Fagopyrum esculentum in different concentrations was carried out to test the allelopathic potential on Euphorbia heterophylla seeds. As a general result, the aqueous extract of Chenopodium quinoa, (10%) presented greater allelopathic potential than the other extracts in the variables tested. Subsequently, other experiments were carried out in the field. The first one aimed at raising the population dynamics of weeds occurring in the soybean crop on the cultural remains of different cover plants: A. strigosa, C. intybus, C. quinoa. The results in the field showed that A. strigosa was the one that obtained the most suppression of the weeds in the 26 and 68 DAE of the cover plants and 53 DAE of the soybean crop. Following the field experiment, the potential of soil cover plants in the inhibition of weeds occurring in the soybean crop was evaluated. A. strigosa presents with a better option of soil cover crop and plant inhibition. Also, a multivariate discriminant analysis was carried out to evaluate the percentage of correct classification of the different management techniques and treatments, where four variables were chosen, with discrimination power of oat, chicory, quinoa and fallow, three discriminant functions, representing 100% of the explained variance. The data were analyzed by the F test and comparison between means by the Tukey test (p≤0.05) and multivariate analysis by the fischer linear discriminant method.